The Romantic Critical Thinking: Theoretical Incoherence of a Unitary Movement - Golban, Petru (Mediterranean Journal of Social Sciences, 2012)
The rise of the expressive theory of authorship in the literary movement that we call Romanticism radicalised the ideasthat the artist is a genius and the work of art is autonomous from the actual reality as it results from an imaginary universe whichis specific to a certain artist. Romantic emphasis on subjective experience and the disinterestedness of the creative act was alsoan aspect of its rejection of the principles of Enlightenment and Neoclassicism. Moreover, although time and place specific andemerging in connection to French Revolution and Industrial Revolution, the exponents of Romanticism were escapist rather thanrebellious as to attempt the improvement of the social conditions. These are some of the reasons that have made critics regardRomanticism as an artistic not social movement and be reluctant to speak about a Romantic ideology in Marxist termsconcerning the socio-historical position of literature, especially when referring to the great Romantic literary criticism expressedin Wordsworth’s Preface to Lyrical Ballads, Coleridge’s Biographia Literaria, and Shelley’s Defence of Poetry. These textsrepresent the main concern of the present study, in relation to which the aim of the study is twofold: first, to discern among theideas and principles regarding the origin of poetry, its subject-matter and language, the role of the poet, and poetic imagination,and, second, to present the ways in which these ideas are materialised or not in literary practice, namely in Wordsworth’s TinternAbbey and Shelley’s To a Skylark.